Multi-modality imaging evaluation of recurrent Tako-tsubo syndrome in a patient with coronary artery fibromuscular dysplasia - Yun Cheng; Chenying Lu; Kan Liu (Cardiovascular Ultrasound, 2017)
Abstract Background Integrated bedside and sophisticated cardiac imaging techniques help characterize the discrepancy between myocardial injury and mechanic dysfunction in acute myocardial infarction. Case presentation A 57 year-old woman presented with sudden onset chest pain and ventricular fibrillation after hearing of her brother’s death. The electrocardiography indicated “anterior wall ST segment elevation myocardial infarction”. Coronary angiography ruled out obstructive lesion in the major coronary arteries, but revealed fibromuscular dysplasia of the distal left anterior descending artery. The ventriculography showed remarkable ventricular dilation, which affected much broader myocardium than the culprit vessel supplied. In a subsequent cardiac magnetic resonance study, delayed contrast (gadolinium) image revealed a focal left ventricular (LV) apical infarction. Her LV systolic function normalized within 1 week, except for a residual apical hypokinesis. She developed recurrent chest pain and LV dilation when she was laid off 9 months later. After supportive therapy, her symptoms improved and LV dysfunction normalized again. Conclusions “Tako-tsubo” syndrome can occur recurrently in the heart with pre-existing localized myocardial infarction. Its molecular mechanism and clinical significance warrants further investigation.